The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/polym14132575
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Interlaminar Shear Properties of Fibre-Reinforced Composites under Biaxial Loading: A New Experimental Approach

Abstract: The complexity of biaxial tests and analysis of their results makes it difficult to study the interlaminar shear properties of fibre-reinforced composites, particularly under through-thickness compression, which occurs in thick-walled composite elements. The improvements in experimental methods to study the features of the nonlinear behaviour of composites under biaxial loading is now an important and relevant task in the development aircraft structural elements made of сarbon fibre-reinforced polymers. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Most of literature works calculate the ILSS values based on the peak force reached during the test. 26,28,29 While this value can be accepted for brittle materials, it does not necessarily coincide with the initiation of delaminations in the specimen for more ductile materials as thermoplastic composites. The determination of a crack initiation criterion is of particular importance in the generation of cohesive zone models in recent finite-element solvers.…”
Section: Mechanical Characterisationmentioning
confidence: 99%
“…Most of literature works calculate the ILSS values based on the peak force reached during the test. 26,28,29 While this value can be accepted for brittle materials, it does not necessarily coincide with the initiation of delaminations in the specimen for more ductile materials as thermoplastic composites. The determination of a crack initiation criterion is of particular importance in the generation of cohesive zone models in recent finite-element solvers.…”
Section: Mechanical Characterisationmentioning
confidence: 99%
“…In Nastran, for linear structural analyses, the MAT9 definition [46] allows to assign orthotropic material properties to 3D solid elements. Since the prosthetic material is carbon fibre composite, the definition of orthotropic properties is reasonable [47][48][49]. The fibres confer strength along their length, meaning that the orientation and length of the fibres directly influence the behaviour of the composite material.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Thus, the in-plane Young moduli (E 1 and E 2 ) are assumed equal. As consequence, also ν 13 and ν 23 and G 13 and G 23 are considered equal [47,48]. Table 6 outlines the orthotropic material properties that best describe the dynamic behaviour of the component after an iterative tuning phase.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…They determined the interlaminar shear modulus, as well as other elastic properties, at predefined load levels by utilising supporting finite element analyses (FEA). Several authors found a V-notched specimen in combination with DIC for strain measurement to be suitable for determining quasi-static shear characteristics [10][11][12].…”
Section: Introductionmentioning
confidence: 99%